Isoperla vjosae sp. n., a new species of the Isoperla tripartita group from Albania (Plecoptera: Perlodidae) - Graf, Wolfram; Pauls, Steffen U.; Vitecek, Simon (Zootaxa, 2018)
In this contribution, we describe Isoperla vjosae sp. nov. from Albania. We characterize males, females, and larvae of the new species collected at the Vjosa River using morphological and molecular approaches. Isoperla vjosae sp.nov. is a member of the I. tripartita group, which is widely distributed in the Balkans. This new endemic species is being threatened by a proposed hydroelectric power dam on the Vjosa River impacting the type locality – a large, shifting gravel, low altitude River – an atypical habitat for larvae of the I. tripartita group. For the first time we use molecular tools to delineate Isoperla species from the Balkans.